Usefulness of serum hyaluronic acid levels as a predictor of incidence of hand osteoarthritis analyzed by longitudinal analysis from the Iwaki cohort - Tatsuro Saruga (Nature Portfolio, 2021)
Abstract The factors predicting hand osteoarthritis (HOA) in patients remain unknown. We aimed to investigate the usefulness of serum hyaluronic acid (sHA) levels in predicting HOA progression from a 6-year longitudinal epidemiological study. A total of 417 participants in the Iwaki cohort were followed-up over 6 years. Hand and knee radiographs taken at baseline and follow-up were scored according to Kellgren–Lawrence grades and Kallman score. Participants were classified into the HOA group and the non-HOA group. sHA levels at baseline were determined by ELISA. Correlations between sHA levels, the number of involved joints, and Kallman score were estimated. Factors related to the incidence or progression of HOA over 6 years were analyzed. The prevalence of HOA was 19.9% at baseline, and 3.6 ± 2.1 joints were involved. sHA levels in the HOA group at baseline were significantly higher than in the non-HOA group (p < 0.001) and correlated with the number of involved joints (r = 0.399, p < 0.001) and Kallman score (r = 0.540, p < 0.001). The incidence rate was 14.5%, and the progression rate was 46.1% over 6 years. Higher sHA levels at baseline were the risk factor of HOA incidence. Thus, sHA levels predicted the incidence of HOA over 6 years.